Transportation Cost Analysis Using Activity-based Costing in Waste Collection Distribution of ESWKA Waste Bank in Cilegon - Iskandar, Yelita Anggiane; Vikaliana, Resista; Khairunnisa, Nazihah; Muhyi, Lana Salsabila; Pratama, Fikih Urdi; Passasung, Octaviano Rosario; Oktafiani, Intan (Universitas Mercu Buana, 2025)
In this study, the main problem encountered is the calculation to determine the actual operating costs in knowing the profit or deficit experienced by Bank Sampah Eswka is still not available. The ABC method is used to identify costs based on transportation operational activities for waste collection from Bank Sampah Unit (BSU) towards Bank Sampah Induk (BSI). The results showed significant efficiency in the calculation of operational costs with a difference in internal costs with a contract value in the range of IDR 993 to IDR 8,220. Thus, the use of the ABC method helps Bank Sampah Eswka to recognize the achievement of a high level of operational efficiency, which allows them to manage waste distribution and processing at a lower cost compared to contractors. This shows that the existing internal system is effective and efficient.